Seasonal Variability of Surface Currents in Cempi Bay, NTB Based on ADCP and HYCOM Data - Muchammad Iqbal Havis; Mochamad Tri Hartanto; Esa Fajar Hidayat; Agustinus Sembiring; Nabil Nabil (University of Diponegoro, 2026)
This study investigates the seasonal variability of surface currents in Cempi Bay, located on the southern coast of Sumbawa Island, Indonesia. Using Acoustic Doppler Current Profiler (ADCP), the data were collected during the Northwest Monsoon (NWM, February 2023) and Southeast Monsoon (SEM, August 2023), along with surface current data from the Hybrid Coordinate Ocean Model (HYCOM), we analyzed tidal and residual current dynamics at two observation points. Harmonic analysis revealed that during the NWM, currents at the eastern inner bay (ADCP-01) were predominantly tidal (76.83%), while in the western inner bay (ADCP-02), residual currents (52.30%) slightly exceeded tidal contributions. Conversely, during the SEM both stations experienced more balanced contributions in approximately 59% at both locations, with residual current influence increasing to 40–41%. HYCOM data depict the general direction of currents spatially well, but tend to underestimate at small scales as nearshore. The findings highlight the significant role of both tidal forces and monsoon-driven residual currents in shaping the seasonal surface current dynamics of Cempi Bay, providing a valuable baseline for oceanographic monitoring and coastal management in the region.